1984
DOI: 10.1113/jphysiol.1984.sp015424
|View full text |Cite
|
Sign up to set email alerts
|

Velocity of sarcomere shortening in rat cardiac muscle: relationship to force, sarcomere length, calcium and time.

Abstract: SUMMARY1. The relation between force and velocity was determined in sixteen trabeculae of rat right ventricle as a function of time during a twitch, of sarcomere length and of external Ca2+ concentration, [Ca2+]O. The trabeculae were studied in modifed Krebs-Henseleit solution at 25 'C.2. Force was measured with a semiconductor strain gauge. Sarcomere length was measured with a laser diffraction system. A servomotor system was used in which control could be switched between sarcomere length, muscle length and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
79
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 30 publications
(52 reference statements)
24
79
0
Order By: Relevance
“…Potential sources of error associated with the use of laser diffraction techniques to measure sarcomere length or V0 are Bragg angle reflection artifacts and inhomogeneity of the muscle preparation. We have recently shown that the possible error in the measurement of sarcomere length and V0 that is due to these artifacts is less than 4 % in our measurements (de Tombe & ter Keurs, 1990c (Daniels et al 1984;. We have previously reported a similar relationship in trabeculae from cat and from hypothyroid rat (de Tombe & ter Keurs, 1991 a, b) showing that the sigmoidal relation between Fo and V0 and…”
Section: Muscle Preparation and Electrical Stimiulationsupporting
confidence: 56%
See 2 more Smart Citations
“…Potential sources of error associated with the use of laser diffraction techniques to measure sarcomere length or V0 are Bragg angle reflection artifacts and inhomogeneity of the muscle preparation. We have recently shown that the possible error in the measurement of sarcomere length and V0 that is due to these artifacts is less than 4 % in our measurements (de Tombe & ter Keurs, 1990c (Daniels et al 1984;. We have previously reported a similar relationship in trabeculae from cat and from hypothyroid rat (de Tombe & ter Keurs, 1991 a, b) showing that the sigmoidal relation between Fo and V0 and…”
Section: Muscle Preparation and Electrical Stimiulationsupporting
confidence: 56%
“…If peak twitch force at 1 9 pum sarcomere length diminished more than 10 % per hour, the preparation was discarded. The methods employed to measure peak isometric twitch force (Fo), sarcomere length (SL) and unloaded velocity to sarcomere shortening (V0) have been described in detail before (ter Keurs et al 1980b: Daniels et al 1984;de Tombe & ter Keurs. 1990c; cf.…”
Section: Muscle Preparation and Electrical Stimiulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Early attempts involved the assumption of a model of muscle that had a contractile unit in series with an elastic element, but this was found to be incorrect 2 and a complete characterisation had to wait for the development of the laser diffraction technique for measuring sarcomere length (SL). 3 Sarcomere shortening velocity has an inverse hyperbolic relationship to force (load).…”
Section: Cardiac Muscle Mechanicsmentioning
confidence: 99%
“…With an increased contractility (increased Ca 2+ ), velocity increased at all levels of load. 3 An attempt was made to apply the series elastic model to assessing contractility in patients by measuring V max as dP/dt/P, where dP/dt is the rate of rise of left ventricular pressure (LVP) and P is the LVP. Not only was the model wrong, but which P do you take?…”
Section: Cardiac Muscle Mechanicsmentioning
confidence: 99%